The role of embodied cultural capital on the development of social capital and spiritual health from the perspective of religion and negative Islamic teachings - Fazilat, Ali Asghar (HTS teologiese studies, 2022)
One of the contexts for the development of social capital and spiritual health is cultural capital. The relationship between religion as an independent variable and social capital as a dependent variable has been analysed. This article aims to analyse the role of cultural capital in the development of social capital and spiritual health from the perspective of religion and negative Islamic teachings. This study attempts to answer the question, ‘what is the role of cultural capital on the development of social capital and spiritual health from the perspective of negative Islamic teachings?’ In this article, an attempt has been made to compare the negative aspect of education in the form of the Qur’anic concept of ‘cultivation’, with its positive aspect in terms of principles, approach and method, in order to return to the model arising from Qur’anic and mystical teachings. The research method is descriptive and analytical, and data processing is interpretive and critical. Data collection has been performed utilising documentary and library study methods. The research findings demonstrate that ‘ethics, science, values, norms, rituals and art’ are the most important elements of embodied cultural capital, which are effective in the development of social capital.Contribution: Therefore, there is a substantial relationship between religion, negative Islamic teachings, the development of embodied cultural capital and the development of social capital and spiritual health.